POST-WAXING CARE: EVIDENCE ON SOOTHING AND ANTI-INFLAMMATORY PRODUCTS (International Seven Journal of Multidisciplinary, 2022)
Hair removal is a widely used aesthetic procedure that, despite its hygienic and aesthetic purpose, causes microtrauma and inflammation to the skin, requiring specific care in the post-procedure period. This study aimed to analyze scientific evidence on the use of soothing and anti-inflammatory products in restoring the skin barrier after different hair removal methods. Through a qualitative bibliographic review, national publications from 2013 to 2022 were analyzed, addressing the physiological impacts of hair removal and dermocosmetic strategies to minimize irritation and inflammation. It was found that natural agents such as aloe vera, chamomile, marigold, and andiroba oil show significant efficacy in reducing erythema, burning, and edema, in addition to promoting tissue regeneration and deep hydration. It was also observed that the combination of antioxidants, vitamins, and phytotherapeutic compounds enhances soothing and protective effects. The results highlight the importance of well-structured post-depilation protocols that include cleansing, hydration, antisepsis, and photoprotection, promoting the physiological rebalancing of the skin and preventing complications. It is concluded that the use of soothing and anti-inflammatory products based on scientific evidence represents a safe and effective strategy in contemporary cosmetology, contributing to healthier and more sustainable aesthetic practices.